Marine Mesozoic Biostratigraphy of the Neuquén Basin - Riccardi, Alberto Carlos (2000)
The marine Mesozoic of the Neuquen Basin in central west Argentina is characterized by ammonites and other invertebrates, especially bivalves, brachiopodes and calcareous microfossils. On that basis, Upper Triassic to Oxfordian, and Tithonian to Barremian have been divided in 39 and 18 ammonite assemblage / zones respectively, corresponding to 15 and 4 for bivalves, 15 and 2 for bra- chiopods and 11 and 9 for microfossils.